The Effectiveness of Smart Board Media in Teaching Reading for Junior High School Student - Hasna Topal; Siti Sarah Fitriani; Nira Erdiana (Universitas Syiah Kuala, 2020)
The use of media is really helpful in assisting the teacher in teaching and learning process. However, the effectiveness of smartboard media in teaching reading has not been testified. Thus, the objective of this study is to figure out the effectiveness of smart board media in teaching reading for junior high school students. This study was conducted in Fatih Bilingual School Banda Aceh. Second-grade students from Fatih Bilingual School were chosen as the sample of this study. Two types of tests, which were pre-test and post-test, were the instrument of this study. The data was analyzed by using statistical formula. The methodology of this study was Experimental design. The revealed data showed that the mean score for pre-test and post-test was 73.75 and 78.44 respectively. The comparison of the score between pre-test and post-test was gained through calculating the gain score, which were 2.26. Based on the result of hypothesis testing, the result of t-score in this study was 2.07 and t-table was 2.13. This result indicated that the alternative hypothesis of this study (Ha) is rejected (2.072.13).